2017
DOI: 10.1590/1089-6891v18e-37693
|View full text |Cite
|
Sign up to set email alerts
|

CRANIOMETRIA EM LOBOS-GUARÁ Chrysocyon brachyurus ILLIGER, 1815 (CARNIVORA, CANIDAE)

Abstract: ResumoOs objetivos do presente trabalho foram obter mensurações em crânios de Chrysocyon brachyurus adultos, caracterizar valores craniométricos para a espécie e observar se a classificação craniométrica de cães domésticos é adequada para o lobo-guará. Foram utilizados sete crânios de lobo-guará adultos, sem distinção de sexo. Determinou-se a localização de nove pontos craniométricos utilizados em cães domésticos para o lobo-guará. Os pontos foram referência para as 18 medidas craniométricas utilizadas para o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…An example is the study by Neto et al [62], who qualified the skull type as mesocephalic in the crab-eating fox based on the skull measurements. Numerous studies on craniometry or skull morphology carried out by scientists significantly focused on the cranial ontogenesis and the relationship between the skull form and the developmental, ecological, and evolutionary aspects, although skull types have not been categorized in other Canidae [63][64][65][66][67][68][69][70][71][72][73][74]. This significantly limits correlation studies of the skull mophometry and the orbit morphometry performed by veterinarians specialized in veterinary ophthalmology of wild or captive animals.…”
Section: The Bony Orbitmentioning
confidence: 99%
“…An example is the study by Neto et al [62], who qualified the skull type as mesocephalic in the crab-eating fox based on the skull measurements. Numerous studies on craniometry or skull morphology carried out by scientists significantly focused on the cranial ontogenesis and the relationship between the skull form and the developmental, ecological, and evolutionary aspects, although skull types have not been categorized in other Canidae [63][64][65][66][67][68][69][70][71][72][73][74]. This significantly limits correlation studies of the skull mophometry and the orbit morphometry performed by veterinarians specialized in veterinary ophthalmology of wild or captive animals.…”
Section: The Bony Orbitmentioning
confidence: 99%
“…The capybaras of this study showed a dorsal triangular notch in the outline of the foramen magnum, different to what is reported for Cavia spp., where the foramen magnum has a straight or convex dorsal rim [2]. This notch has already been described in some rodents such as Gambian rat (Cricetomys gambianus) [16], and in other mammals species, such as four-toed hedgehog (Atelerix albiventris) [4], maned wolf (Chrysocyon brachyurus) [23], and dromedaries (Camelus dromedaries) [28]. In dogs, this contour profile of the foramen magnum has already been considered a morphological change present in these animals, however, recent studies consider this fact to be just an anatomical variation that does not cause harm in dogs [13], which is quite common in brachycephalic breeds and therefore has no functional meaning [3].…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the authors focussed on aspects related to the mastigatory force and did not concentrate on craniometric patterns. Furthermore, Santos et al (2017) realized a study with seven maned wolves (Chrysocyon brachyurus), verifying whether the craniometric data collected allows a classification of the skull type after Getty (1986). According to Hofmann-Appollo (2009), various wild canid species present an intermediate skull type, being classified as mesaticephalic and therefore resembling the domestic dogs.…”
Section: Introductionmentioning
confidence: 82%